The Audit Board Audit Authority Upon State-Owned Enterprises - Cahyo Anggoro (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
The Audit Board of Indonesia performs audits on the management and the accountability of state finances, including those implemented by State-Owned Enterprises. This study aims to see the synchronization of various regulations related to the authority of Audit Board in performing state-owned enterprises audit, as well as the audit conducted by the Audit Board on state-owned enterprises in the period of 2012-2017. This research is conducted by using normative legal research method, and data collection are done through library research to find relevant data. Based on the analysis, it is known that first, the regulation of Audit Board authority over state enterprises has been synchronized in several Acts. The audit conduct by The Audit Board is the attribution authority derived from the 1945 Constitution and further regulated in Acts. Second, the implementation of state-owned enterprises audit period 2012-2017 implemented against Persero and Perum with three types of audit, namely financial, performance and a specific purpose audit. Keywords: Audit Board of Indonesia, State-Owned Enterprises, Audit on State Finance